Developing probiotics, prebiotics, and organic acids to control Salmonella spp. in commercial turkeys at the University of Arkansas USA - Guillermo Tellez-Isaias; Christine Vuong; Brittany Graham; Callie Selby; Lucas Graham; Roberto Seas-Cuesta; Thaina Barros; Lesleigh Beer; Makenly Coles; Aaron Forga; Jared Ruff; Xochitl Hernanez-Velasco; et al. (German Journal of Veterinary Research)
In the United States, non-typhoidal Salmonella causes over one million food-borne infections every year and turkey meat contaminated with Salmonella has been associated from the farm to the processing plant. These outbreaks emphasize efforts on decreasing and preventing human illness associated with live poultry contact through comprehensive interventions from farm-to-fork levels. This review article revises the role of the turkey upper respiratory tract, which is now known to play a crucial role in colonization and as a source of contamination, for this remarkable bacterium that has co-evolved to infect plants and animals. Because agriculture represents over 60 % of the economy of the state of Arkansas, the mission of our laboratory over the last 21 years has been to evaluate and develop applied research to help reduce the incidence of Salmonella spp. from commercial turkey operations. A summary of the published research is presented.